1967
DOI: 10.1111/j.2042-7158.1967.tb08080.x
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine and amphetamine metabolism

Abstract: Desipramine (2.5-5 mg/kg) increases the urinary excretion of amphetamine given intraperitoneally at doses of 75-15 mg/kg and it decreases the excretion ofp-hydroxyamphetamine. The rate of removal of brain amphetamine is decreased by desipramine (5 mg/kg, i.p.) when amphetamine is injected intraperitoneally but not when it is injected intracerebrally. It is suggested that desipramine impairs the hydroxylation of amphetamine in the liver thereby increasing the level of circulating amphetamine and eventually of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Similar to the approach of using DA and 5HT transport blockers, the NE transport blocker desmethylimipramine (DMI) might be used to block m-AMPH-induced cortical NE overflow. However, as an inhibitor of p-hydroxylation of AMPH (Consolo et al, 1967;Sulser et al, 1966), DMI has been shown to significantly elevate AMPH levels in the rat brain (Dolfini et al, 1969). Because NE terminals are largely resistant to m-AMPH-induced injury (Brunswick et al, 1992;Seiden and Ricaurte, 1987), no independent measure is available to assess the effectiveness of DMI in blocking m-AMPH's effects on NE terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the approach of using DA and 5HT transport blockers, the NE transport blocker desmethylimipramine (DMI) might be used to block m-AMPH-induced cortical NE overflow. However, as an inhibitor of p-hydroxylation of AMPH (Consolo et al, 1967;Sulser et al, 1966), DMI has been shown to significantly elevate AMPH levels in the rat brain (Dolfini et al, 1969). Because NE terminals are largely resistant to m-AMPH-induced injury (Brunswick et al, 1992;Seiden and Ricaurte, 1987), no independent measure is available to assess the effectiveness of DMI in blocking m-AMPH's effects on NE terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of several species with DMI has been shown to potentiate the central excitatory effects of amphetamine (Carlton, 1961;Stein, 1964;Dolfini, Tansella, Valzelli & Garattini, 1969). The potentiated effects of amphetamine are not related necessarily to inhibition of the reuptake mechanism by DMI, as the antidepressant drugs also inhibit the in vivo hydroxylation of amphetamine, thus increasing the amount of unmetabolized amphetamine in the brain (Consolo, Dolfini, Garattini & Valzelli, 1967;Lewander, 1969). However, the mouse does not metabolize amphetamine by hydroxylation and in this species DMI does not increase the concentration of amphetamine in the brain, nor does it potentiate amphetamine-induced excitation (Dolfini et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…In rats the depletion of brain and heart NA is partly due to the incorporation into the NA storage granules of a metabolite of amphetamine, p-hydroxynorephedrine, as a false transmitter ( GOLDSTEIN & ANACNOSTE 1965;THOENEN et al 1966;GROPPET~ & COSTA 1969a;LEWANDER 1970LEWANDER & 1971aBRODIE 1970;COSTA & GROPPETTI 1970). However, amphetamine caused NA depletion even in rats pretreated with desmethylimipramine (LEWANDER 1968b & 1971a; GROPPETTI & COSTA 1969a), a drug which inhibits p-hydroxylation of amphetamine in rats ( CONSOLO et al 1967;LEWANDER 1968b). In guinea pigs amphetamine is not p-hydroxylated (DRING et al 1970;present study) and p-hydroxynorephedrine (or norephedrine) could not be detected in the guinea pig brain and heart tissues in agreement with GROPPE~TI & COSTA (1969b).…”
Section: Discussionmentioning
confidence: 99%